Peningkatan Keterampilan Masyarakat dalam Pembuatan Mie Ubi Sebagai Upaya Diversifikasi Pangan dan Pemberdayaan Ekonomi di Desa Bonosari Kebumen - Prayoga, Hendra; Novalita, Syanda Rosa; Rahayu, Septiana Budi; Nurjannah, Dita Novita; Saifuddin, Yayang Ahnaf; Syafiqoh, Ataya; Syarifah, Atik Nur; Nurrohman, Haikal Jabar; Laela, Fasyi Khaetul; Maulana, Lutfi; Hanif, Muhammad (Fisip UIN Sunan Gunung Djati Bandung, 2025)
The sweet potato noodle-making workshop in Bonosari Village is a food diversification effort aimed at optimizing local resources while empowering the community economically. This program was implemented using the Asset-Based Community Development (ABCD) approach, focusing on identifying village potential, collaborative planning with the community, and execution based on local strengths. The workshop engaged 30 participants from women's groups (PKK, KWT, and Muslimat), who received training on raw material selection, noodle-making techniques, and marketing strategies. The workshop results indicate that participants successfully acquired and applied the necessary skills for producing sweet potato noodles. Additionally, this program opened opportunities for the community to develop food-based enterprises. Despite challenges such as raw material availability and product marketing, continuous support from various stakeholders can ensure the program's sustainability. Therefore, this workshop is expected to serve as an initial step toward enhancing community skills, promoting food diversification, and fostering economic growth based on local potential.